Greener photocatalysts : Hydroxyapatite derived from waste mussel shells for the photocatalytic degradation of a model azo dye wastewater - Jun Haslinda, Shariffuddin; Jones, Mark Ian; Patterson, Darrell Alec (Elsevier, 2013)
This paper demonstrates for the first time the feasibility of utilising waste mussel shells for the synthesis of hydroxyapatite, Ca10(PO4)6(OH)2 (denoted as HAP) to be used as a greener, renewable photocatalyst for recalcitrant wastewater remediation. HAP was synthesised from Perna canaliculus (green-lipped mussel) shells using a novel pyrolysis-wet slurry precipitation process. The physicochemical properties of the HAP were characterised using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The HAP produced was of comparable quality to commercial (Sulzer Metco) HAP. The synthesised HAP had good photocatalytic activity, whereby methylene blue (a model textile wastewater compound) and its azo dye breakdown products were degraded with an initial rate of 2.5×10-8molL-1min-1. The overall azo dye degradation was nearly 54% within 6h and 62% within 24h in an oxygen saturated feed in a batch reactor using a HAP concentration of 2.0g/L, methylene blue concentration of 5mgL-1, UV irradiation wavelength of 254nm and a stirring speed of 300rpm. The kinetics were well described by three first order reactions in series, reflecting the reaction pathway from methylene blue to azo dye intermediates, then to smaller more highly oxidised intermediates and finally degradation of the recalcitrants. The final two steps of the reaction had significantly slower rates than the initial step (rates constants of 6.2×10-3min-1, 1.2×10-3min-1 and approximately (due to limited data points) 1.6×10-4min-1 for the first, second and third step respectively), which tie in with this mechanism, however it could also indicate that the reaction is either product inhibited and/or affected by catalyst deactivation. FTIR analysis of the post-reaction HAP revealed surface PO43- group loss. Since there is good photocatalytic activity with oxygen in limited and excess supply during the photoreaction, this indicates the possibility of lattice oxygen participation in the photocatalytic reaction, which needs to be characterised more fully. However, overall, these results indicate that the HAP derived from the mussel shells is a promising greener, renewable photocatalyst for the photocatalytic degradation of wastewater components.